γδ T Cells Modulate Myeloid Cell Recruitment but Not Pain During Peripheral Inflammation - Petrović, Jelena; Silva, Jaqueline Raymondi; Bannerman, Courtney A.; Segal, Julia P.; Marshall, Abigail S.; Haird, Cortney M.; Gilron, Ian; Ghasemlou, Nader (Frontiers in Immunology, 2019)
Circulating immune cells, which are recruited to the site of injury/disease, secrete various inflammatory mediators that are critical to nociception and pain. The role of tissue-resident immune cells, however, remains poorly characterized. One of the first cells to be activated in peripheral tissues following injury are γδ T cells, which serve important roles in infection, disease, and wound healing. Using a mouse line lacking these cells, we sought to identify their contribution to inflammatory pain. Three distinct models of peripheral inflammatory pain were used: intraplantar injection of formalin (spontaneous inflammatory pain), incisional wound (acute inflammatory pain), and intraplantar injection of complete Freund’s adjuvant (chronic inflammatory pain). Our results show that absence of γδ T cells does not alter baseline sensitivity, nor does it result in changes to mechanical or thermal hypersensitivity after tissue injury. Myeloid cell recruitment did show differential changes between models of acute and chonic inflammatory pain. These results were consistent in both male and female mice, suggesting that there are no sex differences in these outcomes. This comprehensive characterization suggests that γδ T cells do not contribute to basal sensitivity or the development and maintenance of inflammatory pain.